2007
DOI: 10.1111/j.1462-2920.2006.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Limits of life in MgCl2‐containing environments: chaotropicity defines the window

Abstract: The biosphere of planet Earth is delineated by physico-chemical conditions that are too harsh for, or inconsistent with, life processes and maintenance of the structure and function of biomolecules. To define the window of life on Earth (and perhaps gain insights into the limits that life could tolerate elsewhere), and hence understand some of the most unusual biological activities that operate at such extremes, it is necessary to understand the causes and cellular basis of systems failure beyond these windows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
435
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(453 citation statements)
references
References 50 publications
16
435
1
1
Order By: Relevance
“…The interface was captured and fractionated as described previously (Daffonchio et al, 2006;Hallsworth et al, 2007). Briefly, 10-litre Niskin bottles housed on a rosette with conductivity-temperature-depth sensors were closed when a large increase in conductivity, indicating that the interface had been entered, was observed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interface was captured and fractionated as described previously (Daffonchio et al, 2006;Hallsworth et al, 2007). Briefly, 10-litre Niskin bottles housed on a rosette with conductivity-temperature-depth sensors were closed when a large increase in conductivity, indicating that the interface had been entered, was observed.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfide concentrations were measured photometrically by the methylene blue method (Cline, 1969). Redox potentials (Eh) of unfiltered sample aliquots were measured immediately according to the procedure described by Daffonchio et al (2006) and Hallsworth et al (2007). Major elements including nitrate and ammonia were analyzed by Stayer 1C isocratic chromatography system for routine ion determination (Portlab, Sulmona, Italy).…”
Section: Geochemical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, DHABs in the Mediterranean and Red Sea have provided exciting new insights into novel microbial diversity and have extended our knowledge of environmental factors that define the limits of life (Eder et al, 1999(Eder et al, , 2001Hallsworth et al, 2007). Studies of Discovery, L'Atalante, Urania, Thetis and Bannock basins revealed that DHAB interfaces harbor abundant and diverse microbial communities that include numerous novel candidate divisions that are more productive than most pelagic marine systems (see, for example, Sass et al, 2001;Van Der Wielen et al, 2005;Yakimov et al, 2007;Edgcomb et al, 2009;Stock et al, 2012).…”
Section: Introductionmentioning
confidence: 99%